Chemical constituents from the leaves of Lyonia ovalifolia var. hebecarpa. (October 2020) - Zhang, Hanqi; Zheng, Xiaofeng; Zheng, Guijuan; Teng, Yang; Zhou, Junfei; Yao, Guangmin
Abstract: A phytochemical investigation of the leaves of Lyonia ovalifolia var. hebecarpa (Franch. ex F.B. Forbes & Hemsl.) Chun (Ericaceae) led to the isolation of 22 compounds, including eight diterpenoids (1 –8 ), two sesquiterpenoids (9 and 10 ), two monoterpenoids (11 and 12 ), two iridoids (13 and 14 ), four phenylpropanoids (15 –18 ), and four lignans (19 –22 ). Their structures were determined by spectroscopic data analysis and comparison with literature data. The absolute configuration of bisdeacetylkalmitoxin VI (1 ) was determined by single-crystal X-ray diffraction analysis for the first time. Notably, all the isolates 1 –22 were reported from the genus of Lyonia for the first time, and compounds 9 –12 and 15 –22 were obtained from the Ericaceae family for the first time. The chemotaxonomic significance of compounds 1 –22 was discussed. Graphical abstract: Image 1 Highlights: Twenty-two compounds were isolated from the leaves of Lyonia ovalifolia var. hebecarpa. This is the first report of the crystal structure of bisdeacetylkalmitoxin VI. All the isolates were obtained from the genus of Lyonia for the first time. Twelve compounds were obtained from the Ericaceae family for the first time. The chemotaxonomic significance of all the isolates was discussed.